1995
DOI: 10.1128/jb.177.11.3058-3066.1995
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative and aerobic metabolism in Rhizobium etli

Abstract: Strains of Rhizobium etli, Rhizobium meliloti, and Rhizobium tropici decreased their capacity to grow after successive subcultures in minimal medium, with a pattern characteristic for each species. During the growth of R. etli CE 3 in minimal medium (MM), a fermentation-like response was apparent: the O 2 content was reduced and, simultaneously, organic acids and amino acids were excreted and poly-␤-hydroxybutyrate (PHB) was accumulated. Some of the organic acids excreted into the medium were tricarboxylic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
137
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 44 publications
13
137
0
Order By: Relevance
“…The PHB yields increased with time dependent manner and highest yield 3.6 g/L was obtained after 48 h for growth of B. cereus. The PHB yield decreased to 2.1 at 72 h. According to Bonartseva et al, (1994) the results confirmed the observed maximal PHB accumulation at 48 h. After 48 h there was a decrease in PHB yield and an increase in the viscosity of the medium at 72, 96 and 120 h. After 48 h, then unfavorable conditions of the medium caused the decrease in PHB yield, because the increase in medium viscosity accompany exopolysaccharides production resulting in oxygen transfer limitation, caused the decrease in PHB synthesis, ( Stam et al, 1986a;Tombolini and Nuti, 1989;Encarnacion et al, 1995). The yield decreased at 72 and 120 h although dry cell weight increased at 120 h, the decrease of PHB indicates that the bacteria used PHB as a source of carbon, causing unsuitable conditions due to inadequate nitrogen and carbon sources in the medium.…”
Section: Effect Of Different Ph Values On Phb Productionsupporting
confidence: 77%
“…The PHB yields increased with time dependent manner and highest yield 3.6 g/L was obtained after 48 h for growth of B. cereus. The PHB yield decreased to 2.1 at 72 h. According to Bonartseva et al, (1994) the results confirmed the observed maximal PHB accumulation at 48 h. After 48 h there was a decrease in PHB yield and an increase in the viscosity of the medium at 72, 96 and 120 h. After 48 h, then unfavorable conditions of the medium caused the decrease in PHB yield, because the increase in medium viscosity accompany exopolysaccharides production resulting in oxygen transfer limitation, caused the decrease in PHB synthesis, ( Stam et al, 1986a;Tombolini and Nuti, 1989;Encarnacion et al, 1995). The yield decreased at 72 and 120 h although dry cell weight increased at 120 h, the decrease of PHB indicates that the bacteria used PHB as a source of carbon, causing unsuitable conditions due to inadequate nitrogen and carbon sources in the medium.…”
Section: Effect Of Different Ph Values On Phb Productionsupporting
confidence: 77%
“…To prevent growth arrest by metabolic imbalance in subsequent cultures, MMY was also supplemented with biotin at 1 mg liter Ϫ1 (19). When needed, amino acids or vitamins were added to MMY at the following concentrations (in g ml Ϫ1 ): cobalamin, 0.5; methionine, 100; and nicotinic acid, 12.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids and strains used in this study are described in Table 1. Rhizobium strains were grown at 30ЊC in PY (peptoneyeast) complex medium or minimal medium containing succinate and ammonium chloride as the sole carbon and nitrogen sources (18). Escherichia coli strains were grown at 37ЊC in Luria-Bertani complex medium or at 30ЊC in minimal medium containing 10 mM glucose, 10 mM ammonium chloride or glutamine as the nitrogen source, 11 mM K 2 HPO 4 , 51 mM KH 2 PO 4 , and 4 mM MgSO 4 ⅐ 7H 2 O.…”
Section: Methodsmentioning
confidence: 99%